PERAN BIOPSI HEPAR DALAM MENEGAKKAN DIAGNOSIS IKTERUS OBSTRUKTIF EKSTRA HEPATIK - Sherly M, Yuliana; Widita, Haris; Ardita, IG; Soemohardjo, Soewignjo (journal of internal medicine, 2006)
Obstructive icterus is caused by 2 major group from the intrahepatic and ekstrahepatic and ekstrahepatic. Generally toconfirm clinical diagnosis is done with USG imaging. In which USG easily could differentite the cause of the bile duct (accuracy90%). The mothode of biopsy is only to evaluate the intrahepatic icterus. In certain cases, it is not easy to confirm either itsobstructive icterus extraheaptic or intrahepatic, as the bile duct smetimes to seen clearly on the USG examination, which is toassure the side of obstructive because the distal part of the bile duct difficult to be seen in 30%-50% cases until hepatic biopsy isreduced. Meanwhile the histopatology appearance of extrahepatic icterus are marked by classis changes known as ductulerreaction, which as the oedema of connective tissue, ductular proliferation and neutrofil infiltration. There by here, we report thecase of a man, 53 years old with obstructive icterus, where in the beginning is suspected as intrahepatic cholestasis and the causeof extrahepatic icterus is unknown, then the diagnosis was confirmed with histopatology examination.